A comparative study on haemostatic markers and prothrombotic genes among patients with acute coronary syndrome and stable coronary heart disease. - Abdulah, Wan Zaidah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Background: Stable corornuy artery disease (SCAD) and acute corornuy syndrome (ACS) are expected to be biologically different in their prothrombotic activities. Objectives: The aims of this study were to investigate the association of haemostatic markers, prothrombotic genes and clinical factors between ACS and SCAD. Methodology: A comparative prospective cross sectional study was done at Hospital Universiti Sains Malaysia (HUSM), involving 110 ACS and 55 SCAD patients. Full blood count (FBC), Prothrombin time (PT), activated partial prothrombin time (APTT), fibrinogen level, FVIII assay, von Willebrand factor antigen (vWF:Ag), activated protein C resistance (APC-R) assay and protein Z level (PZ) were performed on all samples. Analysis of a few prothrombotic genes involving methylene tetrahydrofolate reductase (MlHFR), factor V Leiden (FVL) gene mutations, plasminogen activator inhibitor-I (PAI-1) and human platelet antigen (HP A) I a-1 b polymorphisms were done. Results: A total of 165 CHD patients, 129 males and 36 females were recruited. The mean age of the patients was 60.05 years. FVIII, vWF:Ag and fibrinogen levels were significantly increased in ACS group compared to SCAD group ( p-value < 0.0001, < 0.0001 and 0.005 respectively). APTT was significantly shortened in ACS group compared to SCAD group (p-value < 0.0001). Most of the patients had at least one traditional risk factor for CHD. From multiple logistic regression, factors associated with ACS include high vWF:Ag, high FVIII, 2: 2 prothrombotic genes and histoiy of smoking. Sixty two percent of patients were on aspirin during ACS event. Discussion and conclusion: The prothrombotic activities were shown to be enhanced in ACS group. Haemostatic stress factors combined with multiple prothrombotic genes and histoiy of smoking were found to be associated with ACS in this study. These findings explained the different prothrombotic activities seen in SCAD and ACS and the potential of added morbidity during ACS event. In future, prothrombotic biomarkers may be used as predictors for ACS among the SCAD patients. The possibility of aspirin resistance state among these patients should be addressed.